Social marketing of fall prevention classes to older adults through Churches: cluster randomised controlled trial. (7th October 2012) - DiGuiseppi, C; Thoreson, S; Goss, C.; Marosits, M; Lezotte, D; Clark, L
Abstract : Background: Older adult falls are a leading cause of injuries, disability, and death. Participation in balance/strength classes prevents falls, but few older adults take these classes. Aims/Objectives/Purpose: We tested whether marketing of community balance/strength classes to older adults through churches increased participation. Methods: In two study counties, 51 churches were randomly allocated to intervention or control. We partnered with intervention churches to market N'Balance, an 8-week balance/strength class. The social marketing programme highlighted benefits (e.g., independence) and reduced barriers (e.g., cost) to class participation. Participants in all 34 N'Balance classes held in study counties during the 21-month study period were asked age, church attended, and prior classes taken (97% response); 195 first-time N'Balance participants aged 60+ attended study churches. Mean numbers of first-time participants aged 60+, and mean proportions of adults aged 60+ who participated, in intervention vs control churches, were compared using zero-inflated negative binomial regression and Wilcoxon Two-Sample Test, respectively. Results/Outcomes: Intervention (n=26) and control (n=25) churches demonstrated similar size, denomination and other characteristics. The mean number of participants from intervention churches was higher than from control churches (7.0 vs 0.5, RR=11.2 [95% CI 7.5 to 16.8], p<0.0001). The mean proportion of older adults from intervention churches who participated was higher than from control churches (9.8% vs 0.2%; Z=−4.47, p<0.001). Significance/Contribution to the Field: Marketing balance/strength classes through churches effectively motivates older adults to enrol in such classes. Testing the social marketing programme in other locales is needed to determine its wider applicability for promoting balance/strength classes to prevent older adult falls.